TEACHING ENGINEERING SUBJECTS IN MOTHER TONGUE IN MANUU POLYTECHNICS: A CASE STUDY - Dr. Nagaraju Mandly (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The objective of the paper is to find out the uses and challenges of the mother tongue in teaching diploma in engineering course at MANUU Polytechnic, Bangalore. Here, at polytechnic, Bangalore, there are three courses, ECE, CSE and Civil engineering. The intake of each course at is 60 per course per semester. The expected number of students for three years for three courses is 540